Role Of Atmanirbhar Bharat In Revitalisation Of Supply Chain In India - P.V., Dr. Ranjith; Massand, Dr. Ajay (The journal of contemporary issues in business and government, 2021)
The primary objective of the study is to identify various challenges and solutions for the supply chain amidst COVID Pandemic and to determine Atmanirbhar as one of the possible solutions. The study adopts both primary and secondary data to substantiate the concept of Atmanirbhar Bharat. The survey collects data from middle and upper-level managers across industries through the questionnaire method and uses multiple regression techniques for analysis. The study finds a substantial reduction in imports, delays, affected logistics, and impact on investment returns as significant supply chain challenges to Industries. The recommended solutions for supply chain challenges are the use of automation and technology, meeting customers' changing demand, and the use of optimization. Moreover, Being Atmanirbhar opens up a plethora of opportunities to businesses with a rise in costs. The study highlights cases of different industries in India, adopting Atmanirbhar as a revival strategy for make in India.